Honeymoon or consolidation, or both?: Time dependence of democratic durability. Issue 4 (6th June 2016) - Maeda, Ko
Abstract : Much research has been done to identify factors that facilitate or prevent democratic breakdown. Little attention, however, has been paid to the question of whether and how the baseline risk level (after controlling for the impacts of relevant factors) changes over time. Using a flexible parametric survival model, I analyse the duration of 149 democratic periods (1946–2008) and demonstrate that the baseline risk has an inverted-U shape, which provides evidence for the honeymoon effect and democratic consolidation. This finding has an important policy implication for democratic assistance programmes.